2017
DOI: 10.5812/ircmj.13931
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Biochemical Parameters in Patients with Type 2 Diabetes After Twenty-Four Sessions of Aerobic Exercise: A Randomized Controlled Trial

Abstract: Background: Diabetes is a cosmopolitan health problem worldwide, especially in Asia. It is a metabolic disorder originating from insulin secretion deficiency, insulin performance or both. When both factors are involved, abnormal complications may result. Exercise training plays an important role in controlling diabetic parameters, including biomechanical variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
6
0
3
Order By: Relevance
“…Exercise and medication, and diet are considered three significant interventions in diabetic patients [16]. The positive effects of exercise therapy on glucose control, cardiovascular risk factors, and lipid metabolism in diabetic patients are well known.…”
Section: Exercise Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise and medication, and diet are considered three significant interventions in diabetic patients [16]. The positive effects of exercise therapy on glucose control, cardiovascular risk factors, and lipid metabolism in diabetic patients are well known.…”
Section: Exercise Therapymentioning
confidence: 99%
“…Insulin therapy, including pharmacotherapy and lifestyle interventions, is considered conventional treatments for preventing diabetes complaints [16]. In a study carried out by , the effect of electro-acupuncture and routine physiotherapy treatments was compared on patients with DPN, and it was concluded that electro-acupuncture is an effective and safe method in DPN patients [17].…”
Section: Introductionmentioning
confidence: 99%
“…Pada metode aktivitas fisik , ditemukan dalam lima studi bahwa latihan kombinasi, dibandingkan dengan latihan aerobic, resistensi, maupyn latihan peregangan, mmeiliki manfaat yang lebih baik bagi penderita DMT2. Intensitas latihan mempengaruhi profil lipid karena latihan aerobic maupun resistensi intensitas sedang dan jangka waktu yang pendek tidak mengurangi LDL maupun TG (25), hal itu berbeda dengan hasil penelitian dari rahbar (2017) bahwa pelatihan aerobic dengan intensitas sedang dalam waktu 8 minggu mempiliki dampak positif terhadap pengendalian parameter biokimia, yaitu penurunan kadar glukosa darah puasa, tingkat kolesterol, TG maupun LDL (26). Pelatihan latihan aerobik meningkatkan efektivitas perawatan medis pada DMT2.…”
Section: Gambar 1 Diagram Flow Dan Pemilihan Artikelunclassified
“…Hasil beberapa penelitian mengkonfirmasi bahwa latihan fisik adalah alat utama dalam kontrol glikemik dan profil lipid pada pasien diabetes tipe 2. Praktek program aktivitas fisik berkorelasi dengan kontrol glikemik yang lebih baik dan profil lipid karena menurunkan kadar glukosa darah puasa (26,27,29,40,41), dan tingkat postprandial (28,41), hemoglobin terglikasi (HbA1c) (26), resistensi insulin (27,29,40), dan kadar insulin puasa (27,29,40). Selain itu juga diamati penurunan pada kadar Trigliserida (TG) (25,26,40,41) , kolesterol total (26,40,41), High Density Lipoprotein (HDL) (25,41), dan Low Density Lipoprotein (LDL) (25,26,40,41).…”
Section: Gambar 1 Diagram Flow Dan Pemilihan Artikelunclassified
See 1 more Smart Citation